Dynamic simulation of two-tank indirect thermal energy storage system with molten salt. (December 2017) - Li, Xiaolei; Xu, Ershu; Song, Shuang; Wang, Xiangyan; Yuan, Guofeng
Abstract: Thermal energy storage system, which can effectively store solar energy and make a solar power plant generate electricity in cloudy or rainy weather and nighttime, is a key part of a concentrating solar power plant, which makes solar power technology have unique advantages compared with other renewable energy power technology. Two-tank indirect thermal energy storage system with molten salt is most widely used and has been successfully commercialized in the field of solar power. In this passage, a universal dynamic simulation model of two-tank indirect thermal energy storage system with molten salt used for trough solar power plants based on the lumped parameter method is built, and the dynamic processes of thermal energy storage system charge and discharge, and the changes of heat transfer oil outlet temperature in the oil/salt heat exchanger, molten salt temperature and height in the molten salt tank when heat transfer oil mass flow rate has step disturbances are simulated on the STAR-90 simulation platform. The simulation results show that the model can simulate the charge and discharge dynamic characteristics of two-tank indirect thermal energy storage system with molten salt well, which can be good references for the system design, system control and system debugging. Highlights: A universal dynamic simulation model of two-tank indirect thermal energy storage system with molten salt is built. Dynamic processes of thermal energy storage system charge and discharge, and typical disturbance processes are simulated. The temperature change lag of molten salt in molten salt tanks is discovered and discussed.